Smartphone addiction, stress, and depression among university students - Nadia O. Elamin; Juman M. Almasaad; Reem B. Busaeed; Daniah A. Aljafari; Muhammed A. Khan (Elsevier, 2024)
Background: Smartphones represent a fundamental part of daily life. Smartphone overuse may cause psychological problems such as stress, anxiety, depression, cognitive decline, and adverse effects on students' academic activities. Objectives: This study assessed the relationship between problematic smartphone use among university students, stress and depression levels, and other risk factors. Method: A descriptive cross-sectional study was conducted among undergraduate students at (KSAU-HS) in Jeddah from 2019 to 2020. Data was collected using questionnaires containing the Smartphone Addiction Scale short-version to assess problematic smartphone use (PSU) and the Depression, Anxiety, and Stress Scale-21 (DASS-21). Result: The study included 235 students; 64.3 % were female, the mean age was 21.5 years, and the majority were medical students. Problematic smartphone use was significantly more among female students (76.2 %) compared to males (62.8 %). There was a significant increase in the Smartphone Addiction scores with increased depression and stress levels. Female students had significantly higher stress and depression levels, which were significantly associations with PSU. Female medical students had statistically significantly higher PSU (83.5 %) compared to females from other colleges (68.8 %). Depression was significantly more common among students during their first clinical year compared to their preclinical years. Conclusion: The study found high prevalences of smartphone overuse, depression, and stress among university students, particularly female medical students. Positive correlations were found between stress and depression levels and PSU. PSU can be a risk factor or a consequence that worsens preexisting psychiatric problems. Early psychological support with an emphasis on addressing PSU may improve students' mental and psychological well-being.